Urban-rural technology gap in Malaysia: an exploratory study / Maniam Kaliannan, Shahniza Ismail and Nurul Inani - Kaliannan, Maniam; Ismail, Shahniza; Anuar, Nurul Inani Izzati (Faculty of Administrative Science and Policy Studies, 2012)
Information and Communications Technology (ICT) is considered as an important in agenda in the development of a country. Governments all over the world have invested huge amount of money in acquiring latest IT gadgets and infrastructure in order to equip their citizens with the right IT knowledge in order to create a knowledgeable society. Malaysian government has implemented Multimedia Super Corridor (MSC) in the year 1996 with the aim to develop Malaysia towards Vision 2020 i.e. Becoming a fully developed nation. In this regard, government and relevance agencies trying to educate Malaysians the importance of IT in their daily life in the context of education, working, social life and economy development. However, there is still a huge gap between the people who are IT savvy and with those who are not IT savvy; this gap is known as digital divide. The aim of this study is to look at the level of technology acceptance among urban and rural community of Malaysia. For this purpose, Sepang District, Selangor was selected as for urban area and Lundu District in Sarawak was selected for rural community. A total of 230 completed questionnaires were collected and the Statistical Package for the Social Science (SPSS) was used to analyze the data and to answer the research objectives. Overall findings of the studies show that both Sepang and Lundu are not backward in term of technology acceptance and in the comparison; people at Lundu have scored higher in terms of technology acceptance. Number of recommendations was proposed to relevant authorities in order to empower Malaysians to learn and accept IT as part of their daily life, thus preparing them towards becoming knowledgeable society.